Animación 3d sobre el uso de las señales de tránsito, para establecer un sistema de seguridad vial en el sector de “La Estación” de la ciudad de Latacunga en el período 2015 - Cuzco Villagómez, Washington Mauricio (2016)
The present research project has the finally of inform and sensitize to the people about the proper use of the transit signals in the sector of "LA ESTACION" of Latacunga city, conditionally for being a commercial sector with influx high traffic of pedestrian and vehicular, which is prone to suffer vials incidents, It is why that previous to a registry of place, through surveys, interviews, visual records, etc., It has been possible to verify a high index of road mishaps related to factors external, such as the illegibility , misinformation or just recklessness of drivers and pedestrians that pass daily for the sector mentioned before.